Axisymmetric vacuum fields in general projective relativity - Singh T.; Singh G.P. (My University, 2025)
A method has been derived which enables one to obtain solutions to the stationary, axially symmetric vacuum fields in general projective relativity developed by Arcidiacono from known solutions of the vacuum field in Einstein's theory. The analogue of the Kerr solution in general projective relativity has been obtained as an example. Finally, a relation between the stationary and static axially symmetric vacuum fields in general projective relativity has been derived. © 1989 Plenum Publishing Corporation.